Effects of Chemical Reaction and Heat Generation on MHD Boundary Layer Flow of a Moving Vertical Plate with Suction and Dissipation - Venkateswarlu, M.; Reddy, G.V. Ramana; Lakshmi, D. V. (Engineering International, 2013)
In this paper, the study of the steady two-dimensional flow of an incompressible viscous fluid with heat and mass transfer and MHD heat generation past a moving vertical plate with suction in the presence of viscous dissipation and chemical reaction is investigated. Using similarity variables, the governing partial differential equations are transformed into non-linear ordinary differential equations. These equations are then solved numerically using fourth order Runge-Kutta method with shooting technique. The flow variables are presented graphically. The graphs showed that velocity rises for increasing Grashof number, mass Grashof numer, suction, heat generation and Eckert number while reducing with increasing magnetic parameter, Schmidt number, and chemical reaction parameter and Prandtl number. Comparisons with previously published work are performed and are found to be in an excellent agreement.